Synthesis of Diverse Heterocyclic Scaffolds by (3+3) and (3+4) Cycloannulations of Donor‐Acceptor Vinylcyclopropanes. Issue 1 (18th October 2021) - Faltracco, Matteo; Strähler, Sebastian; Snabilié, Demi; Ruijter, Eelco
Abstract: Palladium‐catalyzed (3+3) and (3+4) cycloannulations between vinylcyclopropanes and various (hetero)aromatic aldehydes are reported. The use of phosphonate‐substituted vinylcyclopropanes provides access to a variety of bi‐ or tricyclic heteroaromatic scaffolds via an allylation/olefination cascade. The nature of the mechanism was investigated by various control experiments. Abstract :